National Embeddedness and Calculative HRM in US Subsidiaries in Europe and Australia - Gooderham, Paul; Nordhaug, Odd; Ringdal, Kristen (SAGE, 2006)
This article presents a study of the degree to which national institutional settings impact on the application of management practices in foreign subsidiaries of multinational companies. Applying the national business systems approach our study centres on the use of calculative human resource management (HRM) practices by subsidiaries of US multinational companies in the UK, Ireland, Germany, Denmark/Norway and Australia, respectively, in comparison with these countries’ indigenous firms.The analysis indicates that while US subsidiaries adapt to the local setting in terms of applying calculative HRM practices, they also diverge from indigenous firm practices.
Keywords: comparative and cross-cultural HRM; human resources and industrial relations; management; performance appraisal and feedback; strategic and international management